2021
DOI: 10.1371/journal.pcbi.1008810
|View full text |Cite
|
Sign up to set email alerts
|

A network-informed analysis of SARS-CoV-2 and hemophagocytic lymphohistiocytosis genes’ interactions points to Neutrophil extracellular traps as mediators of thrombosis in COVID-19

Abstract: Abnormal coagulation and an increased risk of thrombosis are features of severe COVID-19, with parallels proposed with hemophagocytic lymphohistiocytosis (HLH), a life-threating condition associated with hyperinflammation. The presence of HLH was described in severely ill patients during the H1N1 influenza epidemic, presenting with pulmonary vascular thrombosis. We tested the hypothesis that genes causing primary HLH regulate pathways linking pulmonary thromboembolism to the presence of SARS-CoV-2 using novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 103 publications
7
14
0
1
Order By: Relevance
“…This supports the concept that the pathophysiology of HLH does not only involve T cell, NK cell and macrophage dysregulation but also the hyperactivation of neutrophils. In accordance with our findings, it has recently been demonstrated that neutrophils accumulate in inflamed tissues of HLH and COVID-does not return to a homeostatic level due to an ineffective T cytotoxic response 18,19 . Thus, maintaining the immunogenic stimulus for more cytokine/chemokine secretion, which promotes the sustained neutrophil recruitment and consequent tissue damage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This supports the concept that the pathophysiology of HLH does not only involve T cell, NK cell and macrophage dysregulation but also the hyperactivation of neutrophils. In accordance with our findings, it has recently been demonstrated that neutrophils accumulate in inflamed tissues of HLH and COVID-does not return to a homeostatic level due to an ineffective T cytotoxic response 18,19 . Thus, maintaining the immunogenic stimulus for more cytokine/chemokine secretion, which promotes the sustained neutrophil recruitment and consequent tissue damage.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, it represents the first attempt to systems characterize the common signaling pathways and molecular networks shared by COVID-19 and HLH. In agreement with the recent observation that neutrophil hyperactivation plays a key role in the severity of COVID-19 [81][82][83][84] and HLH 18,19 , our approach indicates that COVID-19 and HLH have a common transcriptional profile formed predominantly by a group of regulatory molecules related to cytokine/chemotaxis and by a group of effector molecules that are linked to neutrophil hyperactivation and disease severity. These data highlight the dual role of neutrophils in providing essential antimicrobial functions, but also initiating tissue injury caused by immune dysregulation 85,86 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This creation of gaps can result in microvascular leak and pleural effusion [21][22][23] . Moreover, HLH was also described in severely ill patients during the COVID-19 pandemic, presenting with vascular injury resulting from hyperin ammation in the alveoli [24] . In one study, Weaver et al [25] reported that hyperin ammation, rather than hemophagocytosis, appears to be the driving cause of HLH pathology.…”
Section: Discussionmentioning
confidence: 99%